Films, Affective Computing and Aesthetic Experience: Identifying Emotional and Aesthetic Highlights from Multimodal Signals in a Social Setting - Kostoulas, Theodoros; Chanel, Guillaume; Muszynski, Michal; Lombardo, Patrizia; Pun, Thierry (Frontiers in ICT, 2017)
Over the last years affective computing has been strengthening its ties with the humanities, exploring and building understanding of people's responses to specific artistic multimedia stimuli. 'Aesthetic experience' is acknowledged to be the subjective part of some artistic exposure, namely, the inner affective state of a person exposed to some artistic object. In this work we describe ongoing research activities for studying the aesthetic experience of people when exposed to movie artistic stimuli. To do so, this work is focused on the definition of emotional and aesthetic highlights in movies and studies the people responses to them using physiological and behavioural signals, in a social setting. In order to examine the suitability of multimodal signals for detecting highlights we initially evaluate a supervised highlight detection system. Further, in order to provide an insight on the reactions of people, in a social setting, during emotional and aesthetic highlights, we study two unsupervised systems. Those systems are able to (a) measure the distance among the captured signals of multiple people using the dynamic time warping algorithm and (b) create a reaction profile for a group of people that would be indicative of whether that group reacts or not at a given time. The results indicate that the proposed systems are suitable for detecting highlights in movies and capturing some form of social interactions across different movie genres. Moreover, similar social interactions during exposure to emotional and some types of aesthetic highlights, such as those corresponding to technical or lightening choices of the director, can be observed. The utilisation of electrodermal activity measurements yields in better performances than those achieved when using acceleration measurements, whereas fusion of the modalities does not appear to be beneficial for the majority of the cases.